2009
DOI: 10.1177/1403494808090632
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of intention to use condoms among Sub-Saharan African youth: The applicability of the theory of planned behaviour

Abstract: Aims: To test the applicability of an extended version of the theory of planned behaviour for the study of condom use intentions among large samples of young people in South Africa and Tanzania. Methods: Baseline data of a randomized controlled trial of school-based HIV/AIDS prevention programmes were used. The setting comprised secondary schools in the regions of Cape Town, Polokwane and Dar es Salaam. Participants were 15,782 secondary school students. The main measures were scales for intentions, knowledge,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
74
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(87 citation statements)
references
References 21 publications
(30 reference statements)
10
74
3
Order By: Relevance
“…Self-and instrumental efficacy, beliefs that favour condom use, and supportive peer norms are positively correlated with condom use. 21,[52][53][54][55][56][57][58][59][60][61][62][63][64][65][66][67] Although it is widely acknowledged that the perception that one is susceptible to an STI such as HIV is necessary to motivate preventive action, perception of susceptibility to HIV infection has produced mixed and what appear to be contradictory, influences on condom use. 24,63,[66][67][68] Difficulties in establishing time ordering in the predominantly cross-sectional samples and acknowledgement that perceptions of susceptibility and condom use form a reciprocal relationship of influence have been used to explain these contradictions.…”
Section: Social Cognitions Influencing Condom Usementioning
confidence: 99%
“…Self-and instrumental efficacy, beliefs that favour condom use, and supportive peer norms are positively correlated with condom use. 21,[52][53][54][55][56][57][58][59][60][61][62][63][64][65][66][67] Although it is widely acknowledged that the perception that one is susceptible to an STI such as HIV is necessary to motivate preventive action, perception of susceptibility to HIV infection has produced mixed and what appear to be contradictory, influences on condom use. 24,63,[66][67][68] Difficulties in establishing time ordering in the predominantly cross-sectional samples and acknowledgement that perceptions of susceptibility and condom use form a reciprocal relationship of influence have been used to explain these contradictions.…”
Section: Social Cognitions Influencing Condom Usementioning
confidence: 99%
“…Although the relationship between behavioral intention and actual behavior cannot be accurately measured, the intention to act can be considered as a proximate measure of behavior. Therefore, behavioral intentions can be measured in terms of attitudes, perceived social norms, perceived self-efficacy and perceived severity [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have documented a positive effect of these psychosocial factors on HIV risk behavior among general populations [16][17][18] including female sex workers (FSWs) [19] and their clients [20]. Emp irical research investigating psychosocial correlates of condom use have found that positive attitude towards condom use [5,21], self-efficacy [4,5,16,17,21] and perceived susceptibility to sexually transmitted infections (STIs) [22,23] are positively correlated to condom use practice. A few studies reveal that perceived barriers to condom use and peer norms can hamper condom use practices [18,24].…”
Section: Introductionmentioning
confidence: 99%
“…When Schaalma et al (2009) tested the applicability of the TPB for a study of condom use intentions among 15,782 South African adolescents, they found that consistent with previous studies, that PBC (β = .41) was the strongest predictor, followed by subjective norm (β = .27), then attitude (β = .17). In support of the PBC, the variable that correlated most highly with individuals' intentions to use condoms among 124 undergraduates at Virginia Commonwealth University was PBC (r = .72, p < .01).…”
Section: Support For the Theory Of Planned Behaviorsupporting
confidence: 66%
“…Studies, however, also found that the PBC construct accounted for significant amounts of variance in intentions between 5% to 12% and significantly predicted condom use over subjective norms and attitude (Cha, Kim, & Patrick, 2008;Fazekas, Senn, & Ledgerwood, 2001;Gredig, Nideroest, & Parpan-Blaser, 2007;Heeren, Jemmott, Mandeya, & Tyler, 2007;Jemmott et al, 2007;Kraft, Rise, Sutton, & Roysamb, 2005;Sánchez-García, & Batista-Foguet, 2008;Schaalma et al 2009;Smith & Stasson, 2000;Villarruel, Jemmott, Jemmott, & Ronis, 2007).…”
Section: Support For the Theory Of Planned Behaviormentioning
confidence: 99%